New Deal or raw deal? : how FDR's economic legacy has damaged America - Folsom, Burton W., Jr., 1947- (New York : Threshold Editions, 2009)
"A sharply critical new look at Franklin D. Roosevelt's presidency reveals government policies that hindered economic recovery from the Great Depression -- and are still hurting America today. In this shocking and groundbreaking new book, economic historian Burton W. Folsom exposes the idyllic legend of Franklin D. Roosevelt as a myth of epic proportions. With questionable moral character and a vendetta against the business elite, Roosevelt created New Deal programs marked by inconsistent planning, wasteful spending, and opportunity for political gain -- ultimately elevating public opinion of his administration but falling flat in achieving the economic revitalization that America so desperately needed from the Great Depression. Folsom takes a critical, revisionist look at Roosevelt's presidency, his economic policies, and his personal life. Elected in 1932 on a buoyant tide of promises to balance the increasingly uncontrollable national budget and reduce the catastrophic unemployment rate, the charismatic thirty-second president not only neglected to pursue those goals, he made dramatic changes to federal programming that directly contradicted his campaign promises. Price fixing, court packing, regressive taxes, and patronism were all hidden inside the alphabet soup of his popular New Deal, putting a financial strain on the already suffering lower classes and discouraging the upper classes from taking business risks that potentially could have jostled national cash flow from dormancy. Many government programs that are widely used today have their seeds in the New Deal. Farm subsidies, minimum wage, and welfare, among others, all stifle economic growth -- encouraging decreased productivity and exacerbating unemployment. Roosevelt's imperious approach to the presidency changed American politics forever, and as he manipulated public opinion, American citizens became unwitting accomplices to the stilted economic growth of the 1930s. More than sixty years after FDR died in office, we still struggle with the damaging repercussions of his legacy." -- Book cover.
The making of the myth: FDR and the New Deal -- FDR's rise to power: political skill, ambition, and deception -- What caused the Great Depression? -- The NRA: why price-fixing damaged American business -- The AAA: how it hurt farming -- Relief and the WPA: did they really help the unemployed? -- More public programs that fell short: the Air Mail Act, FERA Camps, and TVA -- Financial interference: manipulation of gold and silver markets, tariffs, stocks, and banks -- Safety net or quagmire? minimum wage, social security, and labor relations -- No free ride: the burden of excise, income, and corporate taxes -- The IRS: FDR's personal weapon -- Patronage transformed: the elections of 1934 and 1936 -- FDR stumbles: court packing, the purge, and the issue of race -- How FDR's deception tarnished the presidency forever -- What FDR should have done: cut spending, tax rates, and the tariff -- What finally did end the Great Depression? -- Why historians have missed the mark -- The New Deal and repercussions for today's economy.
Originally published: 2008.
Includes bibliographical references (p. [311]-312) and index.
Keywords: Roosevelt, Franklin D. -- 1882-1945.; United States -- Economic policy -- 1933-1945.; New Deal, 1933-1939.; Depressions -- 1929 -- United States; United States -- Politics and government -- 1933-1945.; United States -- Economic conditions -- 1918-1945.; Roosevelt, Franklin D. -- 1882-1945.; Economic policy -- United States; New Deal, 1933-1939.; Great Depression, 1929-1939 -- United States; United States -- Politics and government; United States -- Economic conditions